The Effect of Organizational Culture and Good Corporate Governance Mechanism on Human Resource Disclosure - Nadya Natalia Rorong; Lodovicus Lasdi (Institute of Research and Community Outreach - Petra Christian University, 2020)
Human resource is an important and valuable asset to reach competitive advantage for every firms. In the banking and insurance firms, human resource have an important role that is irreplaceable in the operational process of the firms. Human resource disclosure is an activity to disclose information about recruitment process, benefits, training and development program for employee. Therefore, human resource disclosure may provide additional information for the management and all the stakeholders in the development process of decision making. Factors that may affect the human resource disclosure are organizational culture, institutional ownership, and independent commissioner. The objective of this study is to investigate the effect of organizational culture, institutional ownership, and independent commissioner to human resource disclosure. The research’s object are banking and insurance companies that listed in Indonesian Stock Exchange in 2016-2018, there were 55 companies which have been selected by purposive sampling technique. Data were analysed by using multiple regression analysis. Based on the analysis, the results show that organizational culture has positive impact to human resource disclosure. Therefore, institutional ownership and independent commissioner does not affect the human resource disclosure